A study of dermatological disorders with primary psychiatric illness from South India - D., Jeena Dixon; Rajagopal, Rajesh (International Journal of Research in Dermatology, 2020)
Background: Dermatological disorders are frequent among patients with psychiatric illness. The interaction between skin and mind is complex. Pre-existing skin diseases may be modified in psychiatric illness due to self induced changes which may delay the diagnosis and treatment of skin diseases and result in complications. There are only few published studies about skin diseases in psychiatric patients from south India. We are undertaking this study to highlight the importance of dermatology consultation in psychiatric patients. Methods: 200 patients with primary psychiatric disorders who accepted for the study were subjected to history taking and general examination. Detailed dermatological examination was carried out by visual inspection and clinical examination. Results: Out of 200 patients, 65 were diagnosed with major depressive disorder, 42 patients were with bipolar disorder, 40 with schizophrenia, 30 with obsessive compulsion disorder, 23 with anxiety disorder. 153 (76.5%) patients had dermatological findings, in which 84 (55%) had infectious disease, 35 (22.9%) had parasitic infections, 26 (17%) had fungal infections, 15 (9.8%) had bacterial infections, 8 (5.23%) had viral infections. 56 (36.6%) had non-infectious skin findings, 22 (14.4%) had acne, 15 (9.8%) had pruritis, 12 (7.84%) had eczema, 5 (3.3%) had psoriasis and 2 (1.3%) had vitiligo. 13 (8.4%) patients had psychodermatological problems, 10 (6.53%) had neurotic excoriation, 2 (1.3%) had delusion of parasitosis and 1 (0.6%) had trichotillomania. Conclusions: This study implies that there is a definite association of dermatology and psychiatry.